Automated assessment of redox potentials for dyes in dye-sensitized photoelectrochemical cells. Issue 1 (8th December 2021) - Belić, Jelena; Förster, Arno; Menzel, Jan Paul; Buda, Francesco; Visscher, Lucas
Abstract : The alignment of the GSOP, calculated with the adiabatic approach for large number of dyes, with the limitations of a hypothetical system – the CB edge of TiO2 semiconductor and highest oxidation potential of Ru-based WOC. Abstract : Sustainable solutions for hydrogen production, such as dye-sensitized photoelectrochemical cells (DS-PEC), rely on the fundamental properties of its components whose modularity allows for their separate investigation. In this work, we design and execute a high-throughput scheme to tune the ground state oxidation potential (GSOP) of perylene-type dyes by functionalizing them with different ligands. This allows us to identify promising candidates which can then be used to improve the cell's efficiency. First, we investigate the accuracy of different theoretical approaches by benchmarking them against experimentally determined GSOPs. We test different methods to calculate the vertical oxidation potential, including GW with different levels of self-consistency, Kohn–Sham (KS) orbital energies and total energy differences. We find that there is little difference in the performance of these methods. However, we show that it is crucial to take into account solvent effects as well as the structural relaxation of the dye after oxidation. Other thermodynamic contributions are negligible. Based on this benchmark, we decide on an optimal strategy, balancing computational cost and accuracy, to screen more than 1000 dyes and identify promising candidates which could be used to construct more robust DS-PECs.